Future Living: Exploring decarbonization in a mixed-use development for Waterfall Cit - Tsang, Chun (University of the Witwatersrand, Johannesburg, 2024)
In this human-dominated ecosystem, the intensive use of fossil fuels is increasing carbon emis- sions. The environmental implications have emerged as a worldwide concern. Despite extensive research on the reduction of carbon emissions, this issue remains a persistent dilemma, with energy generation for transport and built environment sectors being the largest contributors. Cur- rent solutions, such as using batteries for energy storage, introduces additional sustainability problems. In built environment, sustainability is often overlooked in comfortable lifestyle develop- ments. This research explores alternative approaches through qualitative methods and proposes a mixed-use development at Waterfall City as a creative outcome. The study investigates the viability of integrating green hydrogen technology to create a comprehensive development that addresses living, working and transportation needs. Through this research, developers will be made aware of the implications of prioritising commercial gain and market appeals over a healthy environment. The outcome is to offer an innovative model that appeals to client and developers seeking forward thinking, sustainable solutions.
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; sustainable mixed-use development; green hydeogen in buildings; public transpor; SDG-11: Sustainable cities and communities